1996
DOI: 10.1002/(sici)1096-9861(19960722)371:2<287::aid-cne8>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting adult CNS cholinergic axons express nile and associate with astrocytic surfaces expressing neural cell adhesion molecule

Abstract: To assess the cellular and molecular substrates for cholinergic axon growth in the adult central nervous system (CNS), we implanted grafts of control and nerve growth factor (NGF)-producing genetically modified fibroblasts within the striatum of rats. Sprouting cholinergic axonal processes that grew into grafts of NGF-producing fibroblasts were fasciculated and followed the surface of astrocytic processes for long distances within the grafts. The close and long distance anatomical relationship between the spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 71 publications
1
8
0
1
Order By: Relevance
“…However, other data show that reactive astrocytes can serve as a permissive substratum for axonal regeneration. If resting astrocytes produce low levels of nerve growth factor (NGF), reactive astrocytes have been reported to produce significantly larger amounts (Strauss et al, 1994; Wu et al, 1998) and NGF was shown to induce axonal sprouting in vivo (Chalmers et al, 1996). Furthermore, regenerating axons expressing the adhesion molecule L1 can be supported by reactive astrocytic processes expressing NCAM.…”
Section: The Janus Face Of Neuroinflammation and Its Contribution To mentioning
confidence: 99%
“…However, other data show that reactive astrocytes can serve as a permissive substratum for axonal regeneration. If resting astrocytes produce low levels of nerve growth factor (NGF), reactive astrocytes have been reported to produce significantly larger amounts (Strauss et al, 1994; Wu et al, 1998) and NGF was shown to induce axonal sprouting in vivo (Chalmers et al, 1996). Furthermore, regenerating axons expressing the adhesion molecule L1 can be supported by reactive astrocytic processes expressing NCAM.…”
Section: The Janus Face Of Neuroinflammation and Its Contribution To mentioning
confidence: 99%
“…Among the neuroprotective effects of the glial scar are the physical isolation of the injured area or the internalization of β-amyloid peptides observed in Alzheimer's disease (Dong and Benveniste, 2001); release of nerve growth factor (NGF) that induces axonal sprouting (Strauss et al, 1994;Wu et al, 1998;Chalmers et al, 1996); and release of anti- Fig. 2.…”
Section: Astrocyte and Synapse Dysfunction: Implications For Neurologmentioning
confidence: 99%
“…L1 is among several growth-associated genes that are upregulated by neurons after nervous system injury (Daniloff, et al, 1986;Chaisuksunt et al, 2000;Kubasak et al, 2005), however its effects are contradictory. Some studies suggest that L1 CAM reiterates its developmental role following injury, as it is upregulated on sprouting and regenerating axons in many models (Daniloff et al, 1986;Martini and Schachner, 1988;Miragall et al, 1989;Styren et al, 1995;Chalmers et al, 1996;Brook et al, 2000;Kubasak et al, 2005;Chen et al, 2007). However, other studies conclude that L1 is not essential for axonal growth into the injury site (Jakeman et al, 2006) and that nerve growth factor-induced sprouting is even reduced by co-expression of L1 (Chaudhry et al, 2006).…”
Section: Nih Public Accessmentioning
confidence: 99%